Community Extension Programs and Professional Development of Public Elementary School Teachers - Warrin Magno; Josephine Baguio (International Journal of Transformative Multidisciplinary Studies, 2026)
This study examined the association between community extension programs and professional development among public elementary school teachers in Manay South District, Davao Oriental, Philippines. A descriptive-correlational design involved 134 teachers selected through convenience sampling. Data were obtained through a validated survey that assessed health and environment, literacy, and livelihood initiatives, together with planning, executing, and evaluating dimensions of professional development. Community extension programs were rated high overall (M = 3.51, SD = 0.75), while professional development was also high (M = 3.71, SD = 0.63). The variables showed a strong positive correlation (r = 0.78, p < .001). Multiple regression indicated that health and environment, literacy, and livelihood initiatives were significant predictors of professional development, with livelihood initiatives reporting the largest standardized coefficient (beta = 0.23). The model explained 61% of the variance in professional development (R2 = 0.61, F = 87.92, p < .001). These findings support structured community engagement as a context-responsive avenue for teacher learning.